Nitrogen and phosphorus co-doped hollow carbon microspheres as well as preparation method and application thereof

By preparing nitrogen-phosphorus co-doped hollow carbon microspheres as cathode materials, the problems of insufficient cycle performance and rate performance of room temperature sodium-sulfur batteries have been solved, and the battery's high-efficiency cycle stability and rate performance have been improved, making it suitable for industrial applications.

CN119306204AActive Publication Date: 2025-01-14SOUTH CHINA UNIV OF TECH

Patent Information

Application Number
CN202411368429.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-14
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

Room temperature sodium-sulfur batteries have shortcomings in terms of cycle performance, rate performance, and coulombic efficiency, mainly due to the insulating properties and low reactivity of sulfur, as well as the 'shuttle effect' and volume expansion problems of polysulfides.

Method used

Nitrogen-phosphorus co-doped hollow carbon microspheres were used as the cathode material. They were prepared by copolymerization, coating, sintering and phosphoric acid modification, and then combined with sublimed sulfur to form a cathode material. The hollow structure and nitrogen-phosphorus co-doped carbon shell provide buffer and active sites.

Benefits of technology

It significantly improves the cycle stability and rate performance of room temperature sodium-sulfur batteries, making them suitable for large-scale industrial production and application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306204A_ABST
    Figure CN119306204A_ABST
Patent Text Reader

Abstract

The invention discloses nitrogen and phosphorus co-doped hollow carbon microspheres as well as a preparation method and application thereof. The preparation method of the nitrogen and phosphorus co-doped hollow carbon microspheres comprises the following steps: 1) preparing carboxylated polystyrene microspheres; (2) preparing a ZIF-8 coated carboxylated polystyrene microsphere; (3) preparing nitrogen-doped hollow carbon microspheres; 4) preparing phosphoric acid modified nitrogen-doped hollow carbon microspheres; and 5) sintering the phosphoric acid modified nitrogen-doped hollow carbon microspheres. The nitrogen and phosphorus co-doped hollow carbon microspheres can well adapt to sulfur volume expansion, provide adsorption sites of polysulfide and promote rapid conversion of the polysulfide, and the preparation method is simple, low in production cost and suitable for industrial production. The room-temperature sodium-sulfur battery which is assembled after the cathode material is prepared by compounding the cathode material with sublimed sulfur has excellent cycling stability and rate capability, and is suitable for large-scale industrial production and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of room temperature sodium-sulfur batteries, and in particular to a nitrogen-phosphorus co-doped hollow carbon material and a preparation method and application thereof. Background Art

[0002] Room temperature sodium-sulfur batteries have the advantages of high energy density, low cost, abundant raw material reserves, and green raw materials. They have shown great development potential and have become a highly anticipated chemical energy storage device in recent years. However, due to the insulation and low reactivity of sulfur, the "shuttle effect" of polysulfides, and the huge volume expansion, room temperature sodium-sulfur batteries have obvious shortcomings in cycle performance, rate performance, and coulombic efficiency, and their practical applications are greatly limited.

[0003] Therefore, it is of great significance to develop a positive electrode carrier material that can effectively solve the "shuttle effect", adapt to the volume expansion of sulfur, and has high conductivity. Summary of the invention

[0004] The purpose of the present invention is to provide a nitrogen-phosphorus co-doped hollow carbon microsphere and a preparation method and application thereof.

[0005] The technical solution adopted by the present invention is:

[0006] A method for preparing nitrogen and phosphorus co-doped hollow carbon microspheres comprises the following steps:

[0007] 1) dispersing styrene, methyl methacrylate and acrylic acid in a solvent for copolymerization to obtain carboxylated polystyrene microspheres;

[0008] 2) dispersing carboxylated polystyrene microspheres, soluble zinc salt and 2-methylimidazole in a solvent for reaction to obtain ZIF-8-coated carboxylated polystyrene microspheres;

[0009] 3) placing the ZIF-8 coated carboxylated polystyrene microspheres in a protective atmosphere for sintering to obtain nitrogen-doped hollow carbon microspheres;

[0010] 4) soaking the nitrogen-doped hollow carbon microspheres in a phosphoric acid solution to obtain phosphoric acid-modified nitrogen-doped hollow carbon microspheres;

[0011] 5) The phosphoric acid-modified nitrogen-doped hollow carbon microspheres are placed in a protective atmosphere for sintering to obtain nitrogen-phosphorus co-doped hollow carbon microspheres.

[0012] Preferably, in step 1), the volume ratio of styrene, methyl methacrylate and acrylic acid is 20-40:0.5-2:1.

[0013] Preferably, the solvent in step 1) is water.

[0014] Preferably, the reaction materials in step 1) further include a buffer and an initiator.

[0015] Preferably, the buffer is ammonium bicarbonate.

[0016] Preferably, the initiator is ammonium persulfate.

[0017] Preferably, the copolymerization reaction in step 1) is carried out at a temperature of 70° C. to 90° C., and the reaction time is 10 h to 15 h.

[0018] Preferably, in step 2), the weight ratio of the carboxylated polystyrene microspheres to 2-methylimidazole is 1:5-20.

[0019] Preferably, in step 2), the molar ratio of the soluble zinc salt to 2-methylimidazole is 1:1-5.

[0020] Preferably, the soluble zinc salt in step 2) is at least one of zinc nitrate, zinc sulfate and zinc chloride.

[0021] Preferably, the solvent in step 2) is methanol.

[0022] Preferably, the protective atmosphere in step 3) is a nitrogen atmosphere or an argon atmosphere.

[0023] Preferably, the specific operation of the sintering in step 3) is as follows: heating from room temperature (25°C±5°C) to 800°C-1000°C at a heating rate of 3°C / min-5°C / min, and then keeping the temperature for 1h-3h.

[0024] Preferably, the weight ratio of the solute to the solvent in the phosphoric acid solution in step 4) is 1:20-35.

[0025] Preferably, the solvent in the phosphoric acid solution in step 4) is methanol.

[0026] Preferably, the protective atmosphere in step 5) is a nitrogen atmosphere or an argon atmosphere.

[0027] Preferably, the specific operation of the sintering in step 5) is as follows: heating from room temperature (25°C±5°C) to 400°C-800°C at a heating rate of 8°C / min-10°C / min, and then keeping the temperature for 1h-3h.

[0028] A nitrogen and phosphorus co-doped hollow carbon microsphere is prepared by the above preparation method.

[0029] A positive electrode material comprises sublimated sulfur and the above-mentioned nitrogen and phosphorus co-doped hollow carbon microspheres.

[0030] Preferably, the weight ratio of the sublimated sulfur and nitrogen and phosphorus co-doped hollow carbon microspheres is 1:0.80-1.25.

[0031] A method for preparing the positive electrode material as described above comprises the following steps:

[0032] The sublimated sulfur and nitrogen and phosphorus co-doped hollow carbon microspheres are dispersed in a volatile organic solvent, and then ground until the volatile organic solvent is completely volatilized, and then kept at 150°C to 160°C for 10h to 12h, naturally cooled to room temperature, and then placed in a protective atmosphere at 200°C to 300°C for 20min to 30min to obtain the positive electrode material.

[0033] Preferably, the volatile organic solvent is carbon disulfide.

[0034] Preferably, the protective atmosphere is a nitrogen atmosphere or an argon atmosphere.

[0035] A room temperature sodium-sulfur battery comprises the above-mentioned positive electrode material.

[0036] The beneficial effects of the present invention are as follows: the nitrogen-phosphorus co-doped hollow carbon microspheres of the present invention can well adapt to the volume expansion of sulfur and provide adsorption sites for polysulfides and can promote the rapid conversion of polysulfides, and the preparation method thereof is simple and the production cost is low. The room temperature sodium-sulfur battery assembled after the hollow carbon microspheres are composited with sublimated sulfur to prepare the positive electrode material has excellent cycle stability and rate performance, and is suitable for large-scale industrial production and application.

[0037] Specifically:

[0038] 1) The hollow structure of the nitrogen-phosphorus co-doped hollow carbon microspheres of the present invention is conducive to the loading of sulfur and can provide sufficient buffer space to accommodate the volume expansion of sulfur;

[0039] 2) The nitrogen-phosphorus co-doped carbon shell in the nitrogen-phosphorus co-doped hollow carbon microspheres of the present invention can provide active sites for the adsorption and conversion of polysulfides;

[0040] 3) The preparation method of the nitrogen and phosphorus co-doped hollow carbon microspheres of the present invention is simple and has low production cost, and is suitable for large-scale industrial production and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 TEM and SEM images of the nitrogen and phosphorus co-doped hollow carbon microspheres in Example 1.

[0042] Figure 2 This is the nitrogen adsorption-desorption isotherm curve of the nitrogen and phosphorus co-doped hollow carbon microspheres in Example 1.

[0043] Figure 3 This is the TGA curve of the positive electrode material in Example 1.

[0044] Figure 4 This is a graph showing the electrochemical performance test results of the CR2032 button battery in Example 1.

[0045] Figure 5 This is the SEM image of the nitrogen and phosphorus co-doped hollow carbon microspheres in Example 2.

[0046] Figure 6 This is a graph showing the electrochemical performance test results of the CR2032 button battery in Example 2.

[0047] Figure 7 This is the SEM image of the nitrogen and phosphorus co-doped hollow carbon microspheres in Example 3.

[0048] Figure 8 This is a graph showing the electrochemical performance test results of the CR2032 button battery in Example 3.

[0049] Fig. 9 This is the SEM image of the nitrogen-doped hollow carbon microspheres in the comparative example.

[0050] Fig.10 This is a graph showing the electrochemical performance test results of the CR2032 button battery in the comparative example. DETAILED DESCRIPTION

[0051] The present invention will be further explained and illustrated below in conjunction with specific embodiments.

[0052] Embodiment 1:

[0053] A nitrogen and phosphorus co-doped hollow carbon microsphere, the preparation method of which is as follows:

[0054] 1) 21 mL of styrene, 1.1 mL of methyl methacrylate, 0.92 mL of acrylic acid and 0.49 g of ammonium bicarbonate were dispersed in 100 mL of ultrapure water, and then the temperature was raised to 70°C, 0.53 g of ammonium persulfate was added, and then the temperature was raised to 80°C and stirred for 12 h at a constant temperature, centrifuged, and the solid was washed with water and freeze-dried to obtain carboxylated polystyrene microspheres (denoted as PS);

[0055] 2) 0.3 g of carboxylated polystyrene microspheres and 3.284 g of 2-methylimidazole were added to 100 mL of methanol, and ultrasonically dispersed for 30 min. Then, 1.487 g of zinc nitrate pre-dissolved in 100 mL of methanol was added dropwise. After the addition, stirring was continued for 16 h, centrifuged, and the solid was taken to obtain ZIF-8-coated carboxylated polystyrene microspheres (denoted as PS@ZIF-8);

[0056] 3) The ZIF-8-coated carboxylated polystyrene microspheres were placed in a tubular furnace and filled with argon for protection, and then heated from room temperature to 910°C at a heating rate of 5°C / min, and then kept at this temperature for 2h, and then cooled to room temperature with the furnace to obtain nitrogen-doped hollow carbon microspheres (denoted as NHC);

[0057] 4) 1.0 g of nitrogen-doped hollow carbon microspheres were added to a phosphoric acid solution consisting of 0.8 g of phosphoric acid and 20 mL of methanol, stirred at room temperature for 24 h, and then heated to 80 ° C and continued to stir until the solvent was completely evaporated to obtain phosphoric acid-modified nitrogen-doped hollow carbon microspheres (denoted as H3PO4@NHC);

[0058] 5) The phosphoric acid-modified nitrogen-doped hollow carbon microspheres were placed in a tubular furnace and filled with argon for protection, and then heated from room temperature to 600°C at a heating rate of 10°C / min, and then kept warm for 2 hours, and cooled to room temperature with the furnace to obtain nitrogen-phosphorus co-doped hollow carbon microspheres (denoted as P-NHC-600).

[0059] Performance Testing:

[0060] 1) The transmission electron microscope (TEM) and scanning electron microscope (SEM) images of the nitrogen and phosphorus co-doped hollow carbon microspheres (P-NHC-600) in this embodiment are as follows: Figure 1 (a, b and c are TEM images at different magnifications, d, e and f are SEM images at different magnifications).

[0061] Depend on Figure 1 It can be seen that the nitrogen and phosphorus co-doped hollow carbon microspheres in this embodiment have a hollow structure, which is conducive to the loading of sulfur and adapting to the volume expansion of sulfur.

[0062] 2) The nitrogen adsorption-desorption isotherm of the nitrogen-phosphorus co-doped hollow carbon microspheres (P-NHC-600) in this example is as follows: Figure 2 (a is the adsorption amount-relative pressure relationship curve, b is the pore volume-pore width relationship curve).

[0063] Depend on Figure 2 It can be seen that the micropores and mesopores coexist in the nitrogen and phosphorus co-doped hollow carbon microspheres in this embodiment, which can provide space for the accommodation of sulfur.

[0064] A positive electrode material, the preparation method of which is as follows:

[0065] 1.1 g of sublimated sulfur and 0.9 g of the above-mentioned nitrogen and phosphorus co-doped hollow carbon microspheres (P-NHC-600) were stirred and dispersed in 15 mL of carbon disulfide, and then ground until the carbon disulfide was completely volatilized. The temperature was then raised to 155°C and kept warm for 12 hours. The mixture was naturally cooled to room temperature and placed in a tubular furnace, filled with argon for protection, and kept warm at 200°C for 25 minutes to obtain the positive electrode material.

[0066] Performance Testing:

[0067] The thermal gravimetric analysis (TGA) curve of the positive electrode material in this embodiment is as follows: Figure 3 shown.

[0068] Depend on Figure 3It can be seen that the sulfur content of the positive electrode material in this embodiment is 49wt%.

[0069] A room temperature sodium-sulfur battery, the preparation method of which is as follows:

[0070] The room temperature sodium-sulfur battery positive electrode material was made into a positive electrode sheet, metallic sodium was made into a negative electrode sheet, and a 1.0 mol / L sodium perchlorate ethylene carbonate-diethyl carbonate solution (the volume ratio of ethylene carbonate and diethyl carbonate was 1:1) was used as an electrolyte to assemble a CR2032 button battery in an argon-filled glove box.

[0071] Performance Testing:

[0072] The electrochemical performance test results of the CR2032 button battery in this embodiment are as follows: Figure 4 shown.

[0073] Depend on Figure 4 It can be seen that the CR2032 button battery in this embodiment has excellent rate performance, and the discharge specific capacity is as high as 527.5 mAh / g even at a discharge rate of 3C.

[0074] Embodiment 2:

[0075] A nitrogen and phosphorus co-doped hollow carbon microsphere, the preparation method of which is as follows:

[0076] The phosphoric acid-modified nitrogen-doped hollow carbon microspheres (same as in Example 1) were placed in a tubular furnace and filled with argon for protection, and then heated from room temperature to 400°C at a heating rate of 10°C / min, and then kept warm for 2h, and cooled to room temperature with the furnace to obtain nitrogen-phosphorus co-doped hollow carbon microspheres (denoted as P-NHC-400).

[0077] Performance Testing:

[0078] 1) The SEM image of nitrogen and phosphorus co-doped hollow carbon microspheres (P-NHC-400) in this embodiment is as follows Figure 5 (a, b and c represent different magnifications).

[0079] Depend on Figure 5 It can be seen that the nitrogen and phosphorus co-doped hollow carbon microspheres in this embodiment have a hollow spherical structure, which is conducive to the loading of sulfur and adapting to the volume expansion of sulfur.

[0080] 2) Prepare CR2032 button battery according to Example 1, and then conduct electrochemical performance test. The test results are as follows: Figure 6 shown.

[0081] Depend on Figure 6 It can be seen that the CR2032 button battery in this embodiment has excellent rate performance, and the discharge specific capacity is as high as 496.5 mAh / g even at a discharge rate of 3C.

[0082] Embodiment 3:

[0083] A nitrogen and phosphorus co-doped hollow carbon microsphere, the preparation method of which is as follows:

[0084] The phosphoric acid-modified nitrogen-doped hollow carbon microspheres (same as in Example 1) were placed in a tubular furnace and filled with argon for protection, and then heated from room temperature to 800°C at a heating rate of 10°C / min, and then kept warm for 2h, and cooled to room temperature with the furnace to obtain nitrogen-phosphorus co-doped hollow carbon microspheres (denoted as P-NHC-800).

[0085] Performance Testing:

[0086] 1) The SEM image of nitrogen and phosphorus co-doped hollow carbon microspheres (P-NHC-800) in this embodiment is as follows Figure 7 (a, b and c represent different magnifications).

[0087] Depend on Figure 7 It can be seen that the nitrogen and phosphorus co-doped hollow carbon microspheres in this embodiment have a hollow spherical structure, which is conducive to the loading of sulfur and adapting to the volume expansion of sulfur.

[0088] 2) Prepare CR2032 button battery according to Example 1, and then conduct electrochemical performance test. The test results are as follows: Figure 8 shown.

[0089] Depend on Figure 8 It can be seen that the CR2032 button battery in this embodiment has excellent rate performance, and the discharge specific capacity is as high as 436.8 mAh / g even at a discharge rate of 3C.

[0090] Comparative Example:

[0091] Nitrogen-doped hollow carbon microspheres (denoted as NHC; same as in Example 1).

[0092] Performance Testing:

[0093] 1) The SEM image of nitrogen-doped hollow carbon microspheres (NHC) in this comparative example is as follows Fig. 9 (a, b and c represent different magnifications).

[0094] Depend on Fig. 9 It can be seen that the nitrogen-doped hollow carbon microspheres in this comparative example present a hollow spherical structure, which is beneficial to the loading of sulfur and adapting to the volume expansion of sulfur.

[0095] 2) Prepare CR2032 button battery according to Example 1, and then conduct electrochemical performance test. The test results are as follows: Fig.10 shown.

[0096] Depend on Fig.10It can be seen that the rate performance of the CR2032 button battery in this comparative example is poor, and the discharge specific capacity is only 327.5 mAh / g when the discharge rate is 3C.

[0097] Based on Examples 1 to 3 and the comparative example, it can be seen that by further introducing phosphorus on the basis of nitrogen-doped hollow carbon microspheres and co-doping nitrogen and phosphorus, the electrochemical performance of the assembled CR2032 button battery can be significantly improved.

[0098] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing nitrogen-phosphorus co-doped hollow carbon microspheres, characterized in that: The following steps are involved: 1) dispersing styrene, methyl methacrylate and acrylic acid in a solvent for copolymerization to obtain carboxylated polystyrene microspheres; 2) dispersing carboxylated polystyrene microspheres, soluble zinc salt and 2-methylimidazole in a solvent for reaction to obtain ZIF-8-coated carboxylated polystyrene microspheres; 3) placing the ZIF-8-coated carboxylated polystyrene microspheres in a protective atmosphere for sintering to obtain nitrogen-doped hollow carbon microspheres; 4) soaking the nitrogen-doped hollow carbon microspheres in a phosphoric acid solution to obtain phosphoric acid-modified nitrogen-doped hollow carbon microspheres; 5) The phosphoric acid-modified nitrogen-doped hollow carbon microspheres are placed in a protective atmosphere for sintering to obtain nitrogen-phosphorus co-doped hollow carbon microspheres.

2. The preparation method according to claim 1, characterized in that: The volume ratio of styrene, methyl methacrylate and acrylic acid in step 1) is 20-40:0.5-2:1; the copolymerization reaction in step 1) is carried out at a temperature of 70° C. to 90° C., and the reaction time is 10 h to 15 h.

3. The preparation method according to claim 1 or 2, characterized in that: The weight ratio of the carboxylated polystyrene microspheres to 2-methylimidazole in step 2) is 1:5-20; the molar ratio of the soluble zinc salt to 2-methylimidazole in step 2) is 1:1-5.

4. The preparation method according to claim 1 or 2, characterized in that: Step 3) The specific operation of sintering is as follows: heating from room temperature to 800°C to 1000°C at a heating rate of 3°C / min to 5°C / min, and then keeping the temperature for 1h to 3h.

5. The preparation method according to claim 1 or 2, characterized in that: Step 5) The specific operation of sintering is as follows: heating from room temperature to 400°C to 800°C at a heating rate of 8°C / min to 10°C / min, and then keeping the temperature for 1h to 3h.

6. A nitrogen-phosphorus co-doped hollow carbon microsphere, characterized in that: Prepared by the preparation method according to any one of claims 1 to 5.

7. A positive electrode material, characterized in that: The invention comprises sublimated sulfur and the nitrogen-phosphorus co-doped hollow carbon microspheres as claimed in claim 6.

8. The positive electrode material according to claim 7, characterized in that: The weight ratio of the sublimated sulfur and nitrogen and phosphorus co-doped hollow carbon microspheres is 1:0.80-1.

25.

9. A method for preparing a positive electrode material according to claim 7 or 8, characterized in that: The following steps are involved: The sublimated sulfur and nitrogen and phosphorus co-doped hollow carbon microspheres are dispersed in a volatile organic solvent, and then ground until the volatile organic solvent is completely volatilized, and then kept at 150°C to 160°C for 10h to 12h, naturally cooled to room temperature, and then placed in a protective atmosphere at 200°C to 300°C for 20min to 30min to obtain the positive electrode material.

10. A room temperature sodium-sulfur battery, characterized in that: Contains the positive electrode material according to claim 7 or 8.

Citation Information

Patent Citations

  • Preparation method for bifunctional catalyst allowing simultaneous production of diglycolic acid and hydrogen as well as product and application of preparation method

    CN109126858A

  • Molybdenum carbide modified hollow nitrogen-doped carbon particles as well as preparation method and application thereof

    CN114956038A

  • Supported nitrogen-phosphorus co-doped iron monatomic difunctional electrocatalyst and application thereof

    CN117334928A

  • Hollow porous carbon particles and their synthetic method

    KR1020160001279A

Cited By

  • A method for preparing hollow carbon microspheres for loading drugs and drug release and application thereof

    CN122682041A